Desenvolvimento e aplicação de um sistema computacional para simulação via método dos elementos finitos do comportamento de estruturas de aço e mistas em situação de incêndio - Jose Carlos Lopes Ribeiro (2009)
Recently, many countries have concerned about analysis and design of structures exposed to fire. In Brazil, the code ABNT NBR 14323:1999 dealing with steel and composite structures is currently being reviewed. The review proposal text for this norm has its basis on European research works and standards (EN 1992-1-2:2004, EN 1993-1-2:2005 and EN 1994-1-2:2005). This norm presents procedures for designingsteel and composite structures in fire condition by test results, advanced methods of structural and thermal analyses and simplified methods. Considering the intrinsic conservatism of the simplified methods, the high costs in testing and the difficulty in having access to computer friendly software that permits advanced analysis, this work had as objective to develop a computer software for simulation of structural behavior under fire condition by transient and nonlinear three-dimensional thermomechanical analysis, based on the Finite Element Method. Several examples of steel and composite structural elements were analyzed. The obtained results were compared and critically evaluated considering the procedures of European standards and results from the technical literature. The computer software proved to be a powerful tool doing advanced nonlinear analysis and providing means of validation for the simplified methods proposed in standards in order to improve and optimize them.